(untitled) (American Journal of Islam and Society, 2015)
In Islam, God’s wondrous creativity is reflected in the unity of design in the widest diversity and beauty of the cosmos. For some Muslims, Islamic art expresses this natural beauty as well as the miracles of God’s creation related in the Qur’an and the prophetic traditions (aḥādīth). This article focuses on Hassan al-Turabi’s perceptions of the arts and the aura of conservative prohibition and cautious permission that surrounds them. For him, the Islamic attitude toward the arts and aesthetics is determined by monotheism (tawḥīd), which entails one’s absolute belief in God’s oneness and the abjuration of anything that might compete with it or with His omnipotence. God has created in beauty a dualistic nature: guidance (belief and faith) and temptation (seduction and aberration) for humanity.